SES EGZERSİZLERİNDEN ŞARKI SÖYLEMEYE GEÇİŞTE YAŞANAN SORUNLAR - (:unkn) unknown (My University, 2017)
Ses eğitimcileri genellikle her şeyden önce şarkıcının teknik başarısını ilk gereklilik olarak görme eğilimindedirler. Ses eğitimi egzersizleri teknik gelişim için çok önemli ve gereklidir. Çünkü sadece bu vokal egzersizleri yaparak tekniği geliştirerek hâkimiyet kuracaklardır. Çalışmada, ses eğitiminde; cümlenin yapısı, diksiyon, range, tessitura, karakterizasyon, duygu yoğunluğu ve şarkı için gereken timbre gibi kavramların, egzersizlerden şarkıya geçişte seçilecek repertuarın belirlenmesinde dikkate alınması gereken faktörler olduğu üzerinde durulmuştur. Bununla beraber teknik ile şarkı söylemenin ilişkisi hakkında pek çok eğitimci bazı şarkı ve aryaları incelemiş ve bu parçalardan değişik cümleleri eğitimde ses egzersizi olarak kullanmıştır. Ancak ses egzersizlerinden şarkı söylemeye geçişte doğru seçim için geçerli bir çözüm önerileri getirilmemiştir. Eldeki çalışma bu alan hakkındaki çalışmaları inceleyerek konuya bazı öneriler getirmek amacı ile yapılmıştır

Vocal trainers tend to see the technical success of a singer as the most important requirement. Exercises in vocal training are very important and necessary for technical development. Because, only these vocal exercises will establish the technical development and competency. But the problems arise as the vocal artist fails to succeed in singing even though he/she achieves such exercises. Structure of sentence, diction, range, tessitura, characterization, emotional intensity and timbre required for the song are the factors that should be considered in order to determine the repertoire to be selected during the transition from exercises to song. The relation between training to sing and singing with a technique was examined by many researchers; especially focusing on some songs and arias; and different sentences of these songs were used in vocal exercises. But, no propositions were made for making the right choice at the stage of transition from vocal exercises to singing. As a result, the songs that vocal trainer will select for technical improvement must be songs that do not contradict with the things acquired by vocal training. Therefore, a trainer should consider the characteristics of singer both in technical and interpretation terms while selecting the repertoire; and should focus on improving the singer in both ways
PROBLEMS IN TRANSITION FROM VOICE EXERCISES TO SINGING
Keywords: Tarih